Use of the virtual platform and its impact on judicial processes in the Republic of Peru (LACCEI, 2024)
The objective of this investigation is to "determine how the use of the virtual platform affects judicial processes in the Republic of Peru", this is because the Judiciary has created a virtual platform at the service of the administration of justice. The methodology applied is of a quantitative approach, for the data collection the survey was used as a technique and as an instrument a coded questionnaire with 22 closed questions to explore issues of satisfaction regarding the use of the virtual platform. The instrument was applied to 160 legal professionals distributed proportionally to all regions of Peru. After that, for data analysis, the information collected was objectively tabulated and thus determine the respective conclusions. It was shown that the use of virtual platforms favors the development of judicial processes, having a favorable impact on the accessibility, versatility, need, interaction, and content of said platform. On the other hand, the Judiciary is recommended to promote the use of the virtual platform in aspects such as request for certificates, forms, virtual classroom In the same way, update the websites and train the officials in the user service.